Option pricing under linear autoregressive dynamics, heteroskedasticity, and conditional leptokurtosis - Christian M. Hafner; Helmut Herwartz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Daily returns of financial assets are frequently found to exhibit positive autocorrelation at lag 1. When specifying a linear AR(l) conditional mean, one may ask how this predictability affects option prices. We investigate the dependence of option prices on autoregressive dynamics under stylized facts of stock returns, i.e., conditional heteroskedasticity: leverage effect, and conditional leptokurtosis. Our analysis covers both a continuous and discrete time framework. The results suggest that a non-zero autoregression coefficient tends to increase the deviation of option prices from Black & Scholes prices caused by stochastic volatility.
urn:nbn:de:kobv:11-10046489
Keywords: C15; C22; G13; 330; option pricing; autoregression; heteroskedasticity; GARCH; leverage effect; conditional leptokurtosis